High-Throughput Urinary Neopterin-to-Creatinine Ratio Monitoring of Systemic Inflammation. (30th December 2019) - Stuart, Charlotte M; Zotova, Elina; Koster, Grielof; Varatharaj, Aravinthan; Richardson, Grace; Cornick, Faye R; Weal, Mark; Newman, Tracey A; Postle, Anthony D; Galea, Ian
Abstract: Background: Systemic inflammation is a marker of ill health and has prognostic implications in multiple health settings. Urinary neopterin is an excellent candidate as a nonspecific marker of systemic inflammation. Expression as urinary neopterin-to-creatinine ratio (UNCR) normalizes for urinary hydration status. Major attractions include ( a ) urine vs blood sampling, ( b ) integration of inflammation over a longer period compared with serum sampling, and ( c ) high stability of neopterin and creatinine. Methods: A high-throughput ultraperformance LC-MS method was developed to measure neopterin and creatinine together from the same urine sample. The assay was applied in several clinical scenarios: healthy controls, symptomatic infections, and multiple sclerosis. Area under the curve was compared between weekly and monthly sampling scenarios. Analysis of a single pooled sample was compared with averaging results from analysis of individual samples. Results: The assay has excellent intraassay and interassay precision, linearity of dilution, and spike and recovery. Higher UNCR was demonstrated in female vs male individuals, older age, inflammatory disease (multiple sclerosis), and symptomatic infections. In healthy controls, fluctuations in inflammatory state also occurred in the absence of symptomatic infection or other inflammatory triggers. Analysis of a single pooled sample, made up from weekly urine samples, integrates inflammatory activity over time. Conclusions: UNCR is a useful biomarker of systemic inflammation. The method presented offers simplicity, speed, robustness, reproducibility, efficiency, and proven utility in clinical scenarios. UNCR fluctuations underline the importance of longitudinal monitoring, vs a single time point, to capture a more representative estimate of an individual's inflammatory state over time.